A Case of a Small Hilar Cyst Derived from the Peribiliary Gland with Compression of the Intrahepatic Bile Duct - Koizumi, Kazuo; Hukohe, Yoshihiro; Murakami, Masahiko; Kusano, Mitsuo; Ishihara, Akira (Nippon Shokaki Geka Gakkai zasshi, 1997)
We report a rare case of a small hilar cyst derived from the peribiliary gland. A 61-year-old man was admitted to our hospital because of right hypochondralgia and vomiting. Abdominal US and CT showed a cystic lesion 2cm in diameter in the medial segment of the liver and dilatation of the peripheral bile ducts in the lateral segment. Laparotomy was performed because endoscopic retrograde cholangiography revealed compression and stricture of the left intrahepatic bile duct. At the operation, a simple liver cyst was found to compress the left intrahepatic bile duct at the liver hilus, and cystectomy was carried out. Histopathologically, this lesion was a hilar cyst derived from the peribiliary gland. When a cystic lesion at the liver hilus is found, a biliary cyst arising from dilatation of the peribiliary gland should be kept in mind for the diagnosis.